Workshop Penyusunan Kisi-Kisi Soal Bagi Guru-Guru SMA PGRI Pekanbaru - Nofriyandi Nofriyandi; Leo Adhar Effendi (Community Education Engagement Journal, 2019)
In order to measure the achievement of students’ competencies, a teacher needs to have the skills to develop various forms of good instruments. One form of the instruments is a test with questions. To have a good instrument, it needs to be analyzed by testing the content validity, construct validity and the reliability of the questions.In compiling the test questions, the plan is also called a grid question that will provide directional guidance. In principle, the grid question that will be carried out is necessary for the expected outcome to be achieved. A careful and conceptual grid question is a guarantee for a teacher in measuring the students’ learning mastery with relevant and representative. If the students' abilities are measurable, information on academic ability and achievement of learning objectives can be obtained. The compiling of the grid question was the solution to the problem above. It was due to the grid question covered the scope and the content of the material to be tested. Therefore, it was necessary to implement an activity of making grid question for teachers of PGRI High School. The method of this activity was a workshop for high school teachers in compiling grid question. The results of this community service show that the motivation and the awareness of teachers about the importance of making good, valid, and reliable grid question were increased.